Size-fractionated PM-bound metals and associated health risks in the densely populated megacity of Southern Vietnam: a preliminary investigation - Le Quoc Hau; Nguyen Duy Dat; Nhung Thi-Tuyet Hoang; Giang Tien Nguyen; Perapong Tekasakul; Racha Dejchanchaiwong; Ly Sy Phu Nguyen (Journal of Atmospheric Chemistry, 2026)

Covalently crosslinked amine-functionalized carbon nanotubes with MXene based cellulose nanofiber lamellae structure for thermoconductive electromagnetic interference shielding materials with enhanced stability and flame retardancy - Chi Thien Nguyen; Tien Thi Cam Vo; Thanh Tung Duong; Thi Tuong Vi Tran; Truong Son Le Vu; Trinh Ngoc Dat; Mai Thi Kieu Lien; Duy Khiem Nguyen; Minh Canh Vu (Chemical Engineering Journal, 2026)

Trace Metal Concentrations in Rainwater, Sources, and Health Risks: A Case Study of Hanoi, Vietnam - Thi Phuong Quynh Le; Nhu Da Le; Thi Thu Ha Hoang; Thi Mai Huong Nguyen; Thi Xuan Binh Phung; Emma Rochelle-Newall; Thi Anh Huong Nguyen; Thi Ngoc Mai Pham; Thi Minh Hanh Pham; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen (International Journal of Environmental Research, 2026)

From forests to chopsticks: Mapping semi-legal wildlife supply chains in Vietnam - Aitor Ibáñez Alonso; Phuc Thien Khoa Nguyen; Trong Dat Cao Tien; Thi Mai Trinh; Daan van Uhm (Ambio, 2026)
The exploitation of wildlife for meat consumption—both legal and illegal—poses major conservation, animal welfare, and public health risks. While scholarship often centers on CITES-listed species, non-CITES species remain underexamined. Focusing on the trade in civets and bamboo rats in Vietnam, this study examines the illegal trade embedded within ostensibly legal businesses using crime script analysis (CSA) to map it through two complementary scripts, one farm-based and one restaurant-based. Drawing on 107 interviews and direct observations, findings reveal that more than half of surveyed facilities (34/63) acknowledged illegal sourcing; eight farms operated outside the regulatory system or maintained unregistered satellite locations; two-thirds of registered farms had earlier operated unregistered; and logbook manipulation was widespread. Ritualized inspections and facilitation payments compounded lax oversight. These procedural dynamics provide a foundation for targeted interventions essential to conservation and zoonotic disease surveillance within a One Health framework.

Improving heavy metal prediction using hybrid feature selection and ensemble learning with multi-source remote sensing in Red River Delta mangroves, Vietnam - Nga Nhu Le; Tien Dat Pham; Neil Saintilan; Thin Nguyen; Thi Minh Hanh Pham; Thi Hong Van Le; Thi Viet Lien Nguyen; Thi Diu Dinh; Tien Duc Pham (International Journal of Remote Sensing, 2026)

A methodological assessment and reflection on member checking as a form of participant validation for conservation social science - Judith J. Rakowski; Trong Dat Cao Tien; Trung Cao Tien; Ha Trang Nguyen; Juan Martin Dabezies; Laure Joanny; Meredith L. Gore (Conservation Biology, 2026)
Qualitative approaches are increasingly applied in conservation social science, yet methodological reflection remains limited. Member checking, a process of returning findings to participants for feedback, is widely recognized outside conservation as a means to enhance rigor and reciprocity, but it is rarely reported in conservation research. This paper assesses and reflects on the implementation of member checking within a participatory study on conservation crime prevention in Pù Mát National Park, Vietnam. The member checking process involved 18 sessions with 88 participants representing community members, park staff, nongovernmental organizations, and university researchers. Member checking was used to revisit and refine preliminary interpretations of data collected during previous fieldwork phases. Findings indicated that the process strengthened credibility, confirmability, dependability, and transferability of results while fostering transparency, accountability, and mutual learning. Challenges related to linguistic diversity, power asymmetries, and logistical constraints revealed limits to its universality as a validation tool. The greatest value of member checking for conservation social science lies not in confirming truth but in fostering iterative dialogue, reflexivity, and shared understanding. Approached as a form of participatory reflection, member checking can help bridge methodological rigor and ethical practice, contributing to more equitable and context‐sensitive conservation social science research. We offer practical recommendations for integrating member checking into conservation projects and helping translate principles of reflexive and participatory research into conservation practice.

An undescribed alkaloid from Crinum latifolium L.: structural elucidation and evaluation of its biological activity - Tuan Anh Hoang Le; Ngo Van Hieu; Nguyen Tien Dat; Vu Thi Trang; Pham Van Cong; Do Thanh Tuan; Vinh Le Ba; Lo Van Xanh; Tran My Linh; Pham Thi Hoe; Le Quynh Lien (Natural Product Research, 2026)

Surface-bound species-dominated peroxymonosulfate activation by an N-doped durian shell biochar-supported CoO/Co3O4/ZrO2 composite with strong electronic coupling for efficient carbamazepine degradation - Nguyen Lan Thanh; Nguyen Nhat Huy; Nguyen Hong Nam; Phan Thi Thuy; Le Viet Ngan; Ta Cong Khiem; Kun-Yi Andrew Lin; Vu Dinh Thao; Le The Son; Tran Viet Thu; Tran Tien Dat; Nguyen Trung Dung (Journal of Environmental Sciences, 2026)

Phytochemical investigation of Vernonia amygdalina Delile - Pham Thi Bich Dao; Le Ba Vinh; Nguyen Tien Dat; Ngo Van Hieu; Chu Van Tan; Pham Van Cong; Nguyen Thi Thanh; Nguyen Hai Dang; Hoang Le Tuan Anh (Biochemical Systematics and Ecology, 2026)

When coping means breaking the rules: Understanding conservation crime through strain - Judith J. Rakowski; Michelle Anagnostou; Trong Dat Cao Tien; Trung Cao Tien; Laure Joanny; Ha Trang Nguyen; James L. Slade; Luan Van Nguyen; Elle Jingjing Xu; Meredith L. Gore (Biological Conservation, 2026)

Phenolic glycosides from Ligusticum wallichii with cytotoxic activity - Ninh Khac Thanh Tung; Nguyen Thi Tu Oanh; Nguyen Thi Minh Hang; Nguyen Thi Thu Ha; Tran My Linh; Vu Huong Giang; Yohan Seo; SeonJu Park; Nguyen Tien Dat; Nguyen Xuan Nhiem; Hyung Min Kim; Ninh Khac Ban (Phytochemistry Letters, 2026)

Distribution of heavy metals in mangrove soils of Red River Delta, Northern of Vietnam - Nhu Nga Le; Kim Thuy Nguyen; Thi Diu Dinh; Thi Minh Hanh Pham; Thi Hong Van Le; Xuan Tung Nguyen; Tien Dat Pham; Tien Duc Pham (Marine Environmental Research, 2026)

Phytochemical investigation of Crinum asiaticum L.: isolation and characterisation of a new dimeric alkaloid and evaluation of acetylcholinesterase inhibition with molecular docking - Le Quynh Lien; Le Ba Vinh; Vu Thi Trang; Ngo Viet Duc; Nguyen Viet Phong; Seo Young Yang; Nguyen Minh Trang; Ngo Van Hieu; Do Thanh Tuan; Nguyen Tien Dat; Tran My Linh; Pham Thi Hoe; et al. (Natural Product Research, 2025)

Quantifying five decades of shoreline change in relation to river sediment supply along the Phu Yen Coast, Central Vietnam - Quang Hao Nguyen; Le Thi Que; Tran Quoc Viet; Tien Dat Pham; Vinh Ngoc Tran; Nguyen Tien Giang; Phong Nguyen Thanh; Duong Tran Anh (Geomorphology, 2025)

Bioaccumulation and distribution of per- and polyfluoroalkyl substances and organophosphate flame retardants in marine organisms from the Vietnamese coast: Links to species traits and environmental exposure - Thao Thi Phuong Pham; Le Pham; Tra Thi Pham; Huong Le-Quang; Thuy Cam Quan; Phuong Thi Pham; Dat Nguyen-Tien; Minh Quang Bui (Marine Pollution Bulletin, 2025)

Diosgenin glycosides from Paris vietnamensis (Takht) H.Li with cytotoxic and inhibitory NO production activities - Le Tuan Anh Hoang; Van Cong Pham; Viet Duc Ngo; Van Hieu Ngo; Van Manh Nong; Ha Phuong Lai; Thanh Tuan Do; Tien Dat Nguyen; Ngoc Tung Nguyen (Natural Product Research, 2025)

Inhibitory nitric oxide production and cytotoxic activities of phenolic compounds from Gnetum montanum Markgr - Hieu Ngo Van; Cong Pham Van; Trang Vu Thi; Duc Ngo Viet; Tai Bui Huu; Dat Nguyen Tien; Minh Bui Quang; Anh Le Tuan; Tinh Phung Thi; Dan Nguyen Van; Hoan Vu Xuan; Anh Hoang Le Tuan (Natural Product Research, 2025)

Reactive extrusion recycling of polymethyl methacrylate to methyl methacrylate and methacrylic acid - Yanfa Zhuang; Tien Dat Nguyen; Mahdi Sharifian; Jean-Luc Dubois; Abdellah Ajji; Gregory Patience (Chemical Engineering Journal, 2025)

How does bias correction impact simulated drought characteristics by Regional Climate Models? - Phuong Nguyen-Ngoc-Bich; Manh-Hung Le; Tan Phan-Van; Thanh Ngo-Duc; Tuan Tran-Bui-Anh; Long Trinh-Tuan; Huong Ngo-Thi-Thanh; Dat Pham-Tien; Fredolin T. Tangang; Liew Juneng; Faye Cruz; Jing Xiang Chung; et al. (Climatic Change, 2025)

Waste artificial marble pyrolysis and hydrolysis - Jacopo De Tommaso; Federico Galli; Tien Dat Nguyen; Yanfa Zhuang; Jean-Luc Dubois; Gregory S. Patience (Waste Management, 2025)

Synthesis and adsorption behavior of Zn₂SiO₄ nanoparticles incorporated with biomass-derived activated carbon as a novel adsorbent in a circular economy framework - Van Thuan Le; Viet Hung Hoang; Hien Y Hoang; Anh Tien Nguyen; Van-Dat Doan; Vy Anh Tran (Biomass and Bioenergy, 2025)

Dioxins and Related Compounds in Sediment and Soil from Craft Villages and Industrial Areas in Northern Vietnam - Xuyen Thi Nguyen; Binh Dinh Chu; Hang Thi Hong Mai; Phuc Anh Nguyen; Tra Thi Thu Nguyen; Dat Tien Nguyen; Minh Quang Bui; Tuan Anh Le Hoang; Minh Binh Tu; Nam Duc Vu (Bulletin of Environmental Contamination and Toxicology, 2025)

Lycopodiaceae herb from Vietnam as a promising medicinal source of natural hupezine and novel huperzine-producing endophytic fungi - Thanh Thi Minh Le; Ha Thi Thu Trinh; Ha Thanh Pham; Dat Tien Nguyen; Giang Hoang Do; Hien Thuy Phan; Tam Duc Le; Ngoc Tung Quach; Tien Quyet Phi; Ha Hoang Chu (Biotechnology Letters, 2025)

Occurrence and ecological risks of antibiotics and antiparasitics in surface water in urban lakes in Hanoi city, Vietnam - Nhu Da Le; Thi Thanh Huyen Dinh; Thi Huong Vu; Phuong Thu Le; Thi Mai Huong Nguyen; Thi Thu Ha Hoang; Emma Rochelle-Newall; Thi Xuan Binh Phung; Thi Thuy Duong; Thi Huyen Trang Luu; Thi Lan Phuong Kieu; Thi Anh Huong Nguyen; et al. (Environmental Science and Pollution Research, 2024)

Enhanced sunlight-driven photocatalysis of non-metal doped zinc oxide via wet impregnation for the removal of organic compounds - Le Minh Huong; Nguyen Minh Dat; Nguyen Thanh Hoai Nam; Hoang An; Nguyen Duy Hai; Phan Nguyen Phu Hung; Nguyen Cong Anh Minh; Nguyen Hung Vu; Ly Tan Nhiem; Nguyen Tien Thang; Nguyen Huu Hieu (Environmental Nanotechnology, Monitoring & Management, 2024)

A review on modification of ZnO for highly photoactive catalyst in sustainable energy production processes - Le Minh Huong; Nguyen Minh Dat; Nguyen Thanh Hoai Nam; Nguyen Duy Hai; Le Tan Tai; Hoang An; Che Quang Cong; Nguyen Tien Dat; Nguyen Huy; Ta Dang Khoa; Tran Dang Khoa; Doan Thi Yen Oanh; et al. (Environmental Nanotechnology, Monitoring & Management, 2024)

Understanding polycyclic aromatic hydrocarbon accumulation in road dust of a tropical megacity in southern Vietnam: Implications on environmental management - Nguyen Duy Dat; Ngo Thi Thuan; Nhung Thi-Tuyet Hoang; Giang Tien Nguyen; Ly Sy Phu Nguyen (Chemosphere, 2024)

Effects of P-solubilizing bacteria Cereibacter sphaeroides ST16 and ST26 on soil fertility, P uptake, and rice yield grown on salt-affected soils under greenhouse conditions - Le Tien Dat; Ngo Vuong Ngoc Bao Tran; Do Thi Xuan; Ly Ngoc Thanh Xuan; Le Thanh Quang; Nguyen Quoc Khuong (Journal of Crop Science and Biotechnology, 2024)

Microbial contamination in a large drinking water reservoir in north Vietnam - Nhu Da Le; Thi Mai Huong Nguyen; Thi Thu Ha Hoang; Emma Rochelle-Newall; Thi Xuan Binh Phung; Thi Minh Hanh Pham; Thi Thuy Duong; Tien Dat Nguyen; Thi Phuong Quynh Le (Aquatic Sciences, 2024)

Flavonoids glycosides from Camellia phanii - Ninh Khac Thanh Tung; Hoang Thi Tuyet Lan; Tran Thuy Nga; Nguyen Thi Mai; Vu Mai Thao; Nguyen Viet Dung; Nguyen Tien Dat; Nguyen Xuan Nhiem; Nguyen Bao Tan; Hyung Min Kim; Jong Seong Kang (Phytochemistry Letters, 2024)

Effective degradation of tetracycline in aqueous solution by an electro-Fenton process using chemically modified carbon/α-FeOOH as catalyst - My Linh Nguyen; Hoang Long Ngo; Thuy Tien Nguyen Hoang; Duc Trung Le; Duy Dat Nguyen; Quang Sang Huynh; Thi Tuyet Trinh Nguyen; Thanh Tung Nguyen; Ruey-Shin Juang (Journal of Environmental Health Science and Engineering, 2024)

Chemical constituents from the heterotrophic marine microalgae Aurantiochytrium sp. SC145 and their antimicrobial activities - Nguyen Thi Thu Thuy; Hoang Thi Minh Hien; Nguyen Cam Ha; Le Thi Thom; Dang Diem Hong; Nguyen Van Thinh; Nguyen Trong Dan; Nguyen Dang Hoi; Vu Thi Loan; Hoang Duc Quang; Dan Thi Thuy Hang; Phan Van Kiem; et al. (Natural Product Research, 2024)

Metal contamination, their ecological risk, and relationship with other variables in surface sediments of urban rivers in a big city in Asia: case study of Hanoi, Vietnam - Thi Xuan Binh Phung; Thi Phuong Quynh Le; Nhu Da Le; Thi Thu Ha Hoang; Thi Mai Huong Nguyen; Emma Rochelle-Newall; Thi Anh Huong Nguyen; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen (Environmental Science and Pollution Research, 2024)

Metabolic and genomic analysis deciphering biocontrol potential of endophytic Streptomyces albus RC2 against crop pathogenic fungi - Ngoc Tung Quach; Thi Hanh Nguyen Vu; Thi Thu An Nguyen; Phuong Chi Le; Hoang Giang Do; Tien Dat Nguyen; Phan Thi Hong Thao; Thi Thanh Loi Nguyen; Hoang Ha Chu; Quyet-Tien Phi (Brazilian Journal of Microbiology, 2023)

Microbial contamination in the coastal aquaculture zone of the Ba Lat river mouth, Vietnam - Nhu Da Le; Thi Thu Ha Hoang; Thi Mai Huong Nguyen; Emma Rochelle-Newall; Thi Minh Hanh Pham; Thi Xuan Binh Phung; Thi Thuy Duong; Thi Anh Huong Nguyen; Le Minh Dinh; Thanh Nghi Duong; Tien Dat Nguyen; Thi Phuong Quynh Le (Marine Pollution Bulletin, 2023)

Corrigendum to “Green synthesis of carbon-doped zinc oxide using Garcinia mangostana peel extract: Characterization, photocatalytic degradation, and hydrogen peroxide production” [J. Clean. Prod. 392 (15 March 2023) 136269] - Le Minh Huong; Che Quang Cong; Nguyen Minh Dat; Nguyen Duy Hai; Nguyen Thanh Hoai Nam; Hoang An; Le Tan Tai; Tran Do Dat; Nguyen Tien Dat; Mai Thanh Phong; Nguyen Huu Hieu (Journal of Cleaner Production, 2023)

Undescribed chalcone and stilbene constituents from Lysimachia baviensis and their anti-inflammatory effect - Nguyen Quang Hung; Nguyen Thi Hong Anh; Nguyen Sinh Khang; Nguyen Thi Thanh Huong; Nguyen Thi Luyenb; Dang Viet Hau; Nguyen Tien Dat (Natural Product Research, 2023)

Green synthesis of carbon-doped zinc oxide using Garcinia mangostana peel extract: Characterization, photocatalytic degradation, and hydrogen peroxide production - Le Minh Huong; Che Quang Cong; Nguyen Minh Dat; Nguyen Duy Hai; Nguyen Thanh Hoai Nam; Hoang An; Le Tan Tai; Tran Do Dat; Nguyen Tien Dat; Mai Thanh Phong; Nguyen Huu Hieu (Journal of Cleaner Production, 2023)

Research and Development Prospects for Sugarcane Industry in Vietnam - Thi-Thao Nguyen; Quoc-Tuan Hoang; Tien-Thanh Nguyen; Tuan-Anh Pham; Anh-Duong Cao; Hong-Duong Pham; Viet-Hung Le; Thu-Trang Vu; Ngoc-Hung Pham; Tien-Cuong Nguyen; Kim-Anh To; Van-Hung Nguyen; et al. (Sugar Tech, 2022)

Polybrominated diphenyl ethers in indoor dusts from industrial factories, offices, and houses in northern Vietnam: Contamination characteristics and human exposure - Lieu Thi Tran; Tien Cao Kieu; Hien Minh Bui; Nghia Trong Nguyen; Thuy Thi Thu Nguyen; Dat Tien Nguyen; Trung Quang Nguyen; Huong Thi Anh Nguyen; Tuyen Huu Le; Shin Takahashi; Minh Binh Tu; Anh Quoc Hoang (Environmental Geochemistry and Health, 2022)

Characteristics of polycyclic aromatic hydrocarbons in ambient air of a tropical mega-area, Ho Chi Minh City, Vietnam: concentration, distribution, gas/particle partitioning, potential sources and cancer risk assessment - Nguyen Duy Dat; Ngo Thi Thuan; Nhung Thi-Tuyet Hoang; Hiep Ngoc Tran; To Thi Hien; Khoi Tien Tran; Moo Been Chang (Environmental Science and Pollution Research, 2022)

Learning from multimodal and multisensor earth observation dataset for improving estimates of mangrove soil organic carbon in Vietnam - Nga Nhu Le; Tien Dat Pham; Naoto Yokoya; Nam Thang Ha; Thi Thu Trang Nguyen; Thi Dang Thuy Tran; Tien Duc Pham (International Journal of Remote Sensing, 2021)

Unsubstituted and Methylated PAHs in Surface Sediment of Urban Rivers in the Red River Delta (Hanoi, Vietnam): Concentrations, Profiles, Sources, and Ecological Risk Assessment - Anh Quoc Hoang; Shin Takahashi; Nhu Da Le; Thi Thu Ha Hoang; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen; Thi Xuan Binh Phung; Thi Anh Huong Nguyen; Huu Tuyen Le; Minh Tue Nguyen; Minh Binh Tu; et al. (Bulletin of Environmental Contamination and Toxicology, 2021)

Plant-derived bioactive compounds produced by Streptomyces variabilis LCP18 associated with Litsea cubeba (Lour.) Pers as potential target to combat human pathogenic bacteria and human cancer cell lines - Ngoc Tung Quach; Quang Huy Nguyen; Thi Hanh Nguyen Vu; Thi Thu Hang Le; Thi Thu Thuy Ta; Tien Dat Nguyen; Thuoc Van Doan; The Van Nguyen; Tat Thanh Dang; Xuan Canh Nguyen; Hoang Ha Chu; Quyet Tien Phi (Brazilian Journal of Microbiology, 2021)

Antibiotic and antiparasitic residues in surface water of urban rivers in the Red River Delta (Hanoi, Vietnam): concentrations, profiles, source estimation, and risk assessment - Nhu Da Le; Anh Quoc Hoang; Thi Thu Ha Hoang; Thi Anh Huong Nguyen; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen; Van Chung Hoang; Thi Xuan Binh Phung; Huu Tuyen Le; Cao Son Tran; Thu Hien Dang; et al. (Environmental Science and Pollution Research, 2021)

The potential health risks and environmental pollution associated with the application of plant growth regulators in vegetable production in several suburban areas of Hanoi, Vietnam - Van Nhan Le; Quang Trung Nguyen; Tien Dat Nguyen; Ngoc Tung Nguyen; Tibor Janda; Gabriella Szalai; Truong Giang Le (Biologia Futura, 2020)

New dammarane-type triterpenoid glycosides from Gynostemma burmanicum - Thi Kieu My Than; Thanh Ky Pham; Thanh Binh Pham; Thao Nguyen Phuong; Dat Nguyen Tien (Natural Product Research, 2020)

Anticyanobacterial phenolic constituents from the aerial parts of Eupatorium fortunei Turcz - Thanh Nga Pham; Huu Dien Pham; Dinh Kim Dang; Thi Thuy Duong; Thi Phuong Quynh Le; Quang Duong Nguyen; Dat Nguyen Tien (Natural Product Research, 2019)

Anti-inflammatory constituents from Psychotria prainii H. Lév - Phi Hung Tran; Viet Dung Le; Thi Ha Do; Thi Luyen Nguyen; Phuong Thao Nguyen; Trong Thong Nguyen; Tien Dat Nguyen (Natural Product Research, 2019)

The in vitro and in vivo anti-inflammatory activities of alphitonin-4-O-β-D-glucopyranoside - Nguyen Quoc Vuong; Vu Van Chien; Do Thi Thao; Nguyen Thi Nga; Do Thi Phuong; Pham Van Cuong; Nguyen Tien Dat (Natural Product Research, 2018)

Antimicrobial and Cytotoxic Properties of Bioactive Metabolites Produced by Streptomyces cavourensis YBQ59 Isolated from Cinnamomum cassia Prels in Yen Bai Province of Vietnam - Hanh-Nguyen Thi Vu; Dat Tien Nguyen; Huy Quang Nguyen; Ha Hoang Chu; Son Ky Chu; Minh Van Chau; Quyet-Tien Phi (Current Microbiology, 2018)

Limonoid from the rhizomes of Luvunga scandens (Roxb.) Buch. Ham - Tan Phat Nguyen; Nhat Phan Minh; Trong Bui Dat; Tien Dung Le; Minh An Tran Nguyen; Thi Nhat Trinh Pham; Dinh Mai Tri (Natural Product Research, 2017)

Impact of metal stress on the production of secondary metabolites in Pteris vittata L. and associated rhizosphere bacterial communities - Hoang Nam Pham; Serge Michalet; Josselin Bodillis; Tien Dat Nguyen; Thi Kieu Oanh Nguyen; Thi Phuong Quynh Le; Mohamed Haddad; Sylvie Nazaret; Marie-Geneviève Dijoux-Franca (Environmental Science and Pollution Research, 2017)

A new dihydrofurocoumarin from the fruits of Pandanus tectorius Parkinson ex Du Roi - Tan Phat Nguyen; Tien Dung Le; Phan Nhat Minh; Bui Trong Dat; Nguyen Kim Tuyen Pham; Thi My Lien Do; Dinh Tuyen Nguyen; Tri Dinh Mai (Natural Product Research, 2016)

A new megastigmane sulphoglycoside and polyphenolic constituents from pericarps of Garcinia mangostana - Thu Huong Tran; Tram Le Huyen; Thi Minh Tran; Tuan Anh Nguyen; Thanh Binh Pham; Dat Nguyen Tien (Natural Product Research, 2016)

A new anti-inflammatory β-carboline alkaloid from the hairy-root cultures of Eurycoma longifolia - Pham Bich Ngoc; Thanh Binh Pham; Hai Dang Nguyen; Thu Trang Tran; Hoang Ha Chu; Van Minh Chau; Jeong-Hyung Lee; Tien Dat Nguyen (Natural Product Research, 2016)

Soluble epoxide hydrolase inhibitory activity by rhizomes of Kaempferia parviflora Wall. ex Baker - Nguyen Phuong Thao; Bui Thi Thuy Luyen; Jang Hoon Kim; Ah Reum Jo; Seo Young Yang; Nguyen Tien Dat; Chau Van Minh; Young Ho Kim (Medicinal Chemistry Research, 2016)

New flavonoid and pentacyclic triterpene from Sesamum indicum leaves - Nguyen Tien Dat; Nguyen Hai Dang; Le Nguyen Thanh (Natural Product Research, 2016)

New C 20 -gibberellin diterpene from the leaves of Schefflera sessiliflora De P. V. - Tan Phat Nguyen; Thi Thao Vy Tran; Dinh Tri Mai; Tien Dung Le; Nhat Minh Phan; Trong Dat Bui (Natural Product Research, 2015)

Toxicity and anticancer effects of an extract from Selaginella tamariscina on a mice model - Le Minh Ha; Do Thi Thao; Hoang Thanh Huong; Chau Van Minh; Nguyen Tien Dat (Natural Product Research, 2012)

Inhibitory effects on nuclear factor κB of the Vietnamese freshwater cyanobacteria - Tien Dat Nguyen; Thi Thuy Duong; Thi Phuong Quynh Le; Van Minh Chau; Minh Ha Le; Dinh Kim Dang; Jung Joon Lee; Marie-Lise Bourguet-Kondracki (Medicinal Chemistry Research, 2011)